Photodynamic Therapy with Protoporphyrin IX Precursors Using Artificial Daylight Improves Skin Antisepsis for Orthopedic Surgeries - Tiziano A. Schweizer; Julia S. Würmli; Julia Prinz; Maximilian Wölfle; Roger Marti; Hendrik Koliwer-Brandl; Ashley M. Rooney; Vanni Benvenga; Adrian Egli; Laurence Imhof; Philipp P. Bosshard; Yvonne Achermann (Microorganisms)
Classical preoperative skin antisepsis is insufficient in completely eliminating bacterial skin colonization for arthroplasty. In contrast, photodynamic therapy (PDT) with red light and methyl-aminolevulinate (MAL), combined with skin antisepsis, led to the absence of bacterial growth in healthy participants, though with local skin erythema, posing an obstacle for orthopedic surgery. Therefore, we explored whether artificial daylight PDT (PDT-DL) was superior to red light. Twenty healthy participants were allocated to either 5-aminolevulinic acid-(5-ALA) PDT-DL (n = 10) or MAL-PDT-DL (n = 10) before antisepsis with povidone-iodine/alcohol. Skin swabs from the groin were taken to cultivate bacteria at baseline, after PDT-DL, and after the subsequent antisepsis. Additional swabs were taken on day 4 before and after antisepsis without PDT. The contralateral groin of each participant and of ten additional healthy volunteers served as the control (n = 30). In selected participants, 16S rRNA-based amplicon deep sequencing was performed. All participants showed a baseline bacterial colonization. After a PDT-DL with skin antisepsis, bacterial growth occurred in three (30%) and in one (10%) participants with 5-ALA and MAL, respectively, compared to the sixteen (55%) participants in the control group. On day 4, three (30%) participants per group showed positive cultures post antisepsis. Adverse effects were reported in six (60%) and zero (0%) participants for 5-ALA- and MAL-PDT-DL, respectively. The skin bacteriome changes correlated with the bacterial culture results. The MAL-PDT-DL with skin antisepsis significantly increased bacterial reduction on the skin without adverse effects. This offers an opportunity to prevent infections in arthroplasty patients and reduce antibiotic use, thus contributing to antibiotic stewardship goals emphasized in the One Health approach.